Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1093/infdis/158.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Initial Characterization of a Ferret Pneumocystis carinii Surface Antigen

Abstract: The purification and initial characterization of a ferret Pneumocystis carinii surface glycoprotein is described. Previous studies have demonstrated that passive administration of monoclonal antibody recognizing this glycoprotein reduces the severity of P. carinii pneumonitis in animal models of infection. This acidic glycoprotein (approximate isoelectric point, 5.0-5.7) contains both mannose (and/or glucose) and N-acetyl-glucosamine residues. The cross-reactive surface antigen on P. carinii of human origin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 8 publications
1
52
0
Order By: Relevance
“…Gigliotti et al (18), using immunoelectron microscopy, demonstrated that MSG is distributed on the surface of all developmental stages of P. carinji. Through molecular studies of rat and ferret P. carindi, it has been demonstrated that MSG represents a group of proteins encoded by multiple genes (6)(7)(8)19). Numerous unique MSG cDNAs have been identified, establishing that multiple mRNAs are transcribed within a population of organisms (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Gigliotti et al (18), using immunoelectron microscopy, demonstrated that MSG is distributed on the surface of all developmental stages of P. carinji. Through molecular studies of rat and ferret P. carindi, it has been demonstrated that MSG represents a group of proteins encoded by multiple genes (6)(7)(8)19). Numerous unique MSG cDNAs have been identified, establishing that multiple mRNAs are transcribed within a population of organisms (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…Two major groups of antigens have been identified in this organism by immunoblotting. One group, which is present as a broad band of 90-120 kDa, has been well-characterized as the major surface glycoprotein (MSG) in Pneumocystis organisms derived from rats, humans, mice, ferrets and rabbits (Graves et al, 1986;Walzer & Linke, 1987;Gigliotti et al, 1988;Kovacs et al, 1989Kovacs et al, , 1993Bauer et al, 1993;Kutty et al, 2001). The second group, which appears as a broad band of 45-55 kDa in P. carinii and 35-45 kDa in human-derived Pneumocystis jiroveci (Stringer et al, 2002), is less well-studied (Walzer & Linke, 1987;Smulian et al, 1992Smulian et al, , 1993Smulian et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Trophic forms do not express ␤-glucan (15). Both stages express surface glycoproteins and mannoproteins, which may serve as pathogen-associated molecular patterns (PAMPs) that could interact with receptors on phagocytic cells (17)(18)(19). Neither life form expresses chitin or ␣-glucans (20).…”
mentioning
confidence: 99%